Heterologous expression of two novel bacteriocins produced by Lactobacillus crustorum MN047 and application of BM1157 in control of Listeria monocytogenes. (April 2018) - Yi, Lanhua; Luo, Lingli; Lü, Xin
Abstract: Foodborne pathogens cause diseases by food chain transmission, therefore preservatives or antimicrobials are essential for food products, among which bacteriocins are considered as promising alternatives of chemical preservatives. Moreover, bacteriocins can potentially be used as antibiotic alternatives. In this study, two genes of novel bacteriocins (BM1157 and BM1300) from probiotic Lactobacillus crustorum MN047 were identified, cloned, and then expressed in Escherichia coli expression system. The genes were inserted into expression vector pET-28a and transformed into competent E. coli BL21 (DE3) pLysS, after which the two bacteriocins were successfully heterologously expressed. Further, it showed that the BM1157 and the BM1300 had broad spectrum activity against gram-positive and gram-negative bacteria, including multidrug-resistant strains. The characteristics and action mode of the BM1157 were further investigated because of its higher antimicrobial activity. It was found that the BM1157 had MIC value of 5.2 μg/mL against both S. aureus and E. coli . Moreover, it was stable at high temperature and resistant to proteinases. The BM1157 had bactericidal action mode according to time-kill curve. The results of scanning electron microscope and transmission electron microscope demonstrated that the BM1157 killed Listeria monocytogenes by biofilm destruction and pore formation. The antibiofilm activity and pore formation were further verified by crystal violet dye and lactic dehydrogenase release. In addition, the BM1157 inhibited the growth of L. monocytogenes in milk. Highlights: Two novel bacteriocins were obtained from probiotic Lactobacillus crustorum MN047. The two bacteriocins were heterologously expressed in E. coli. The two bacteriocins had broad spectrum antimicrobial activity. The BM1157 had bactericidal mechanism by biofilm-destruction and pore-formation.